Local Wisdom Rhetoric In Teacher Character Formation: A Balaghah-Based Instructional Model For Arabic Language Education Students Using Bugis Pappaseng - Haniah Haniah; A-eshah Waemamah; Fachrul Ghazi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This study aims to develop a local-wisdom-based balaghah instructional model as part of the conceptualization of Balaghah Nusantara, integrating classical Arabic rhetorical theory with Bugis cultural values expressed in pappaseng texts. The main problem in university-level Balaghah instruction lies in its cognitive-theoretical orientation, which neglects the affective and character-building dimensions. Employing a Design-Based Research (DBR) approach through design, limited implementation, evaluation, and refinement stages, this study analyzes three principal pappaseng using taḥlīl balāghī (maʿānī–bayān–badīʿ) and pragmatic stylistics methods. The findings reveal that pappaseng contains rhetorical structures such as istiʿārah tamthīliyyah, kināyah ‘an sifah, uslūb al-qasr, and ijāz, which embody the core Bugis values of siri’ (integrity), pacce (empathy), lempu’ (honesty), paccing (purity), and reso’ (diligence). The synthesis led to the formulation of the Local-Wisdom-Based Balaghah Model (BBKL–PBA) or Ethno-Balaghah Pedagogy, positioning pappaseng as a rhetorical reading, value reflection, and discourse-production medium for Arabic language education students. The study concludes that pappaseng Bugis functions as both an epistemic and pedagogical device in forming ethically grounded Arabic language teachers while reinforcing the conceptual foundation of Balaghah Nusantara as a culturally rooted paradigm of Islamic rhetoric.